IMPACT OF SORBITOL- INDUCED OSMOTIC STRESS ON SOME BIOCHEMICAL TRAITS OF POTATO IN VITRO - & et al., Mawia (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study had as principal objective identification of osmotic-tolerant potato genotypes by using "in vitro" tissue culture and sorbitol as a stimulating agent, to induce water stress, which was added to the culture nutritive medium in different concentration (0,50, 110, 220, 330 and 440 mM). The starting point was represented by plantlets culture collection, belonging to eleven potato genotypes: Barcelona, Nectar, Alison, Jelly, Malice, Nazca, Toronto, Farida, Fabulla, Colomba and Spunta. Plantlets were multiplied between two internodes to obtain microcuttings (in sterile condition), which were inoculated on medium. Sorbitol-induced osmotic stress caused a significant reduction in the ascorbic acid, while the concentration of proline, H2O2 and solutes leakage increased compared with the control. Increased the proline content prevented lipid peroxidation, which played a pivotal role in the maintenance of membrane integrity under osmotic stress conditions. The extent of the cytoplasmic membrane damage depends on osmotic stress severity and the genotypic variation in the maintenance of membranes stability was highly associated with the ability of producing more amounts of osmoprotectants (proline) and the non-enzymic antioxidant ascorbic acid in response to osmotic stress level. The results showed that the genotypes Jelly, Nectar, Allison, Toronto, and Colomba are classified as highly osmotic stress tolerant genotypes, while the genotypes Nazca and Farida are classified as osmotic stress susceptible ones.